Bourdieu in Africa : exploring the dynamics of religious fields - Echtler, Magnus. (Studies of Religion in Africa, 2015)
Bourdieu in Africa: Exploring the Dynamics of Religious Fields offers a view of religions as social games played by interested actors. Analyzing practices as strategic moves, this critical approach conceptualizes the religious field as relations of exchange and competition between experts and laity, and explores how the actors' habitus, including religious beliefs, serve to misrecognize and thus legitimize relations of power within the religious sphere and beyond. The authors discuss the volatile religious fields of Nigeria, Ethiopia, Eritrea, Kenya and South Africa, with their variably configured tensions between African traditions, Christianity and Islam, but also consider the interrelations of religion with other social fields, with politics, economy, education and law.